Novel Classification for Upper Tract Urothelial Carcinoma to Better Risk-stratify Patients Eligible for Kidney-sparing Strategies: An International Collaborative Study - Marcq, Gautier; Foerster, Beat; Abufaraj, Mohammad; Matin, Surena F; Azizi, Mounsif; Gupta, Mohit; Li, Wei-Ming; Seisen, Thomas; Clinton, Timothy; Xylinas, Evanguelos; Mir, M Carmen; Schweitzer, Donald; et al. (European urology focus, 2022)
BACKGROUND: The European Association of Urology risk stratification dichotomizes patients with upper tract urothelial carcinoma (UTUC) into two risk categories. OBJECTIVE: To evaluate the predictive value of a new classification to better risk stratify patients eligible for kidney-sparing surgery (KSS). DESIGN, SETTING, AND PARTICIPANTS: This was a retrospective study including 1214 patients from 21 centers who underwent ureterorenoscopy (URS) with biopsy followed by radical nephroureterectomy (RNU) for nonmetastatic UTUC between 2000 and 2017. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: A multivariate logistic regression analysis identified predictors of muscle invasion (≥pT2) at RNU. The Youden index was used to identify cutoff points. RESULTS AND LIMITATIONS: A total of 811 patients (67%) were male and the median age was 71 yr (interquartile range 63-77). The presence of non-organ-confined disease on preoperative imaging (p < 0.0001), sessile tumor (p < 0.0001), hydronephrosis (p = 0.0003), high-grade cytology (p = 0.0043), or biopsy (p = 0.0174) and higher age at diagnosis (p = 0.029) were independently associated with ≥pT2 at RNU. Tumor size was significantly associated with ≥pT2 disease only in univariate analysis with a cutoff of 2 cm. Tumor size and all significant categorical variables defined the high-risk category. Tumor multifocality and a history of radical cystectomy help to dichotomize between low-risk and intermediate-risk categories. The odds ratio for muscle invasion were 5.5 (95% confidence interval [CI] 1.3-24.0; p = 0.023) for intermediate risk versus low risk, and 12.7 (95% CI 3.0-54.5; p = 0.0006) for high risk versus low risk. Limitations include the retrospective design and selection bias (all patients underwent RNU). CONCLUSIONS: Patients with low-risk UTUC represent ideal candidates for KSS, while some patients with intermediate-risk UTUC may also be considered. This classification needs further prospective validation and may help stratification in clinical trial design. PATIENT SUMMARY: We investigated factors predicting stage 2 or greater cancer of the upper urinary tract at the time of surgery for ureter and kidney removal and designed a new risk stratification. Patients with low or intermediate risk may be eligible for kidney-sparing surgery with close follow-up. Our classification scheme needs further validation based on cancer outcomes.
Keywords: senioři; Urologic surgical procedures; Retrospective Studies; nádory močového měchýře; nádory močovodu; Transitional cell carcinoma; karcinom z přechodných buněk; mužské pohlaví; Urological diagnostic techniques; Ureteral Neoplasms; ženské pohlaví; retrospektivní studie; Humans; Risk assessment; Ureteroscopy; ledviny; Urologic neoplasms; Urinary Bladder Neoplasms; Carcinoma, Transitional Cell; Kidney; Female; Aged; lidé; Male